LOWER TO MIDDLE ORDOVICIAN ACRITARCHS AND CHITINOZOANS FROM NORTHERN KARAKORUM MOUNTAINS, PAKISTAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
The lower Vidiakot section (Chitral, Pakistan) comprises the lower part (Yarkhun Formation and the base of the Vidiakot Formation) of the terrigenous complex transgressively overlying the crystalline basement of Northern Karakorum. From this section, 8 of 15 samples contain moderately abundant and poorly preserved acritarchs and rare, badly preserved chitinozoans. Three different palynological assemblages have been distinguished which are referable to the chronological interval early Arenig-earliest Llanvirn. The presence of Arbusculidium, Coryphidium, and Striatotheca in most samples confirms the paleogeographic attribution of the Northern Karakorum Terrane to the northern Gondwana margin (Lower to Middle Ordovician Mediterranean acritarch Palaeoprovince). Refined correlation with other areas and with the previously studied Ishkarwaz section (upper Yarkhun Valley, Chitral) enables the authors the Yarkun Formation to be dated as early Arenig (British lower nitidus graptolite Zone) to latest Arenig (uppermost graptolite hirundo Zone). The base of the overlying Vidiakot Formation is here correlated with the uppermost hirundo- lowermost artus graptolite Zones (latest Arenig-earliest Llanvirn).